The Impact of Political Uncertainty on Asset Prices : The Case of the United Kingdom's EU Membership Referendum. (Washington, D.C. : International Monetary Fund, 2021)
How did expectations of the outcome of the United Kingdom's (UK) referendum on European Union (EU) membership in 2016 affect prices in financial markets? We study this using high frequency data from betting and financial markets. We find that a one percentage point increase in the probability of "Leave" result caused British stocks (FTSE All-Share) to decline by 0.004 percent, and the Pound to depreciate by 0.006 percent against the euro. We find negative and significant effects for most sub-sectors, and negative spill-overs to other EU member countries. We show that the differential impact across sectors and countries can be explained by differences in the trade exposures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Brexit; EU Referendum; High Frequency Data; Information, Knowledge, and Uncertainty; Political Uncertainty; United Kingdom